Between Samizdat and Tamizdat: The Case of the Almanac Fioretti - Kukuj, Ilja (Wiener Slawistischer Almanach, 2021)
The paper focuses on the history of Fioretti (1965), a samizdat almanac of the Malaya Sadovaya poets, one of the first unofficial literary communities in Leningrad in the 1960s. The planned publication of the almanac both in samizdat and tamizdat (particularly, in the journal Grani, affiliated with the NTS) was cancelled for fear of likely persecution by the Soviet authorities. The paper describes the period’s historical and political context and reconstructs the list of contributing authors at the time of its (non)publication, based on archival findings. A comparative analysis of the almanac’s contents with its new edition, published by Mikhail Yupp in Philadelphia in 2017, raises several questions about strategies for canonizing unofficial authors in Soviet times and today.